Pythagorean Fuzzy \((l,u)\)-Level Cuts and Their Applications to Fuzzy Normed Subrings - Adak, Amal Kumar; Kumar, Gauri Kant (Communications in Mathematics and Applications, 2025)
When attempting to quantify an ill-quantity, the Pythagorean Fuzzy Set (PFS) notion is essential. This study provides a \((l,u)\)-level cut of Pythagorean Fuzzy Sets (PFSs). We define \((l,u)\)-level cuts of a PFS \((P)\) as crisp sets consisting of elements \((x)\) for which the membership value is greater than \((l)\) and non-membership value is less than \((u)\). The concept of Pythagorean fuzzy normed subring is introduced and its properties are investigated. Additionally, the relationship between PFNSRs and Pythagorean fuzzy \((l,u)\)-level sets is analyzed.